فعالية استخدام نموذج الارتفاع الرقمي في التحليل المورفومتري للشبكة النهرية في حوض المنطار - سلوم, جولييت; عبدو, حازم (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
This research aims to highlight the Digital Elevation Model, an advanced tool, In the buildingof morphometricvariables geographic database at Al-Mentar basin, and compare them in terms of work and time spent and the results the way, with the use of the traditional way (Topographic Map), right down to morphometricanalysis network in the river basin.The most important results of the research are, proving the effectiveness of a digital elevation model, compared with the use of the traditional method. Showing through, flexible and rapid way of working, and accurate results rules used. As well as the results of morphometric analysis of the network of river in the basin studied, which showed roughness chopping streams river network to the surface of the basin, and the large impact of the lack of the surface of the basin slope and the permeability of the surface layer at various morphometric characteristics, combined with non-affected streams this network by the system basinflaws.يهدف هذا البحث إلى إبراز نموذج الارتفاع الرقمي (Digital Elevation Model)،كأداة متقدمة، في بناء قاعدة بيانات جغرافية ذات خصائص مورفومترية في حوض المنطار، ومفاضلتها من حيث طريقة العمل والوقت المستغرق والنتائج، مع استخدام الطريقة التقليدية (الخريطة الطبوغرافية)، وصولاً إلى التحليل المورفومتري للشبكة النهرية في الحوض.أهم النتائج التي توصّل إليها البحث،إثبات فعالية نموذج الارتفاع الرقمي، بالمقارنة مع استخدام الطريقة التقليدية. تبين ذلك من خلال، طريقة العمل المرنة والسريعة، ودقة نتائج المعاملات المستخدمة. فضلاً عن نتائج التحليل المورفومتري للشبكة النهرية في الحوض المدروس، التي بينت خشونة تقطيع مجاري الشبكة النهرية لسطح الحوض، والتأثير الكبير لقلة انحدار سطح الحوض ونفوذية الطبقة السطحية على مختلف الخصائص المورفومترية، بالتضافر مع عدم تأثّر مجاري هذه الشبكة بمنظومة الحوض الصدعية.